Mitigation and Innovation in Making Natural Handwash Made from Coffee Grounds in Dusun X Batangkuis Deli Serdang Schools Towards Face-to-Face Schools - Elimasni; Nurwahyuni, Isnaini; Supriharti, Deny; Pratama, Rizky Yudha (Talenta Publisher, 2023)
The government's desire to reopen and implement offline education has become a hot topic of discussion lately. The risk of spreading covid 19 to children is the concern of many people. For this reason, mitigation and prevention efforts need to be carried out to reduce the potential for the spread of covid 19. One effort that can be done is to make hand washing a good habit. The activity was carried out by providing training in making liquid hand soap for the community, especially teachers and school students in Dusun X to socialize how to prevent the spread of Covid-19 in schools. Activities are carried out through 5 (five) stages which include (1) Survey (2) Soap Making Test (3) Socialization; (4) Soap-making skills training; (5) Monitoring and Evaluation. It is hoped that the manufacture of natural handwash can be used for schools and school children in Dusun X Batangkuis Deliserdang to prevent covid 19 from going to face-to-face school in 2021.